Adult chicken alpha-globin genes alpha A and alpha D: no anemic shock alpha-globin exists in domestic chickens. - Dodgson, J B (1981)
Three alpha-type globin genes have been identified in the alpha-globin linkage group of chickens. No other alpha-type genes hae been directly shown to be within 10 kilobase pairs of any of these three closely linked genes. These three genes have been conclusively identified by DNA sequence analysis. The gene at the 5' end of the linkage group is an embryonic alpha-type globin gene, pi or pi', and the central gene corresponds to the minor adult alpha- globin, alpha D. The 3'-terminal gene sequence corresponds to the sequence of cDNA clones previously described as "alpha S", presumed anemic shock-induced alpha-globin gene [Salser, W. A., Cummings, I., Liu, A., Strommer, J., Padayatty, J. & Clarke, P. (1979) in Cellular and Molecular Regulation of Hemoglobin Switching, eds. Stamatoyannopoulos, G. & Nienheis, A. (Grune and Stratton, New York), pp. 621-643; Richards, R. I. & Wells, J. R. E. (1980) J. Biol. Chem. 255, 9306-9311]. Several groups of workers have isolated alpha S-type cDNA clones but no one has identified a cDNA clone corresponding to the published amino acid sequence of the major chicken alpha-globin, alpha A. We have identified the alpha S-type sequence as the only abundant alpha-like globin sequence in cDNA clones made from reticulocyte mRNA isolated from nonanemic chickens. Therefore, we suggest that the alpha S-type sequence corresponds to the true alpha A-globin species.